Mathematics in Motion: The Role of Timing, Rhythm, and Patterns in Theatre - Bhuyan, Pallabi (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research explores the intersection of mathematics and theatre, focusing on how mathematical concepts such as timing, rhythm, and patterns influence theatrical performances. Theatre is often perceived solely through an artistic lens, yet it relies heavily on structured frameworks that can be modeled mathematically. Through a mixed-methods approach, this study investigates how mathematical principles are embedded in various elements of theatre, including script structure, choreography, sound, lighting, and blocking. The research draws on examples from classic and contemporary plays, supported by interviews with theatre professionals and data analysis of performance timings and rhythmic elements. This study aims to bridge the gap between the artistic and analytical worlds, offering a new interdisciplinary framework for understanding and enhancing theatrical practice through mathematical thinking.